Analysis of the Development of the Shoe Laundry Application “AHS-CLEAN” - Ong, Danny; Imron, Imron; Nurhayati, M. Sinta; Andriansah, Andriansah (CV. Publikasi Indonesia, 2024)
The era of digitalization where the majority of people prefer to stay at home and are reluctant to do activities is a problem for manual economic movements but provides benefits from the possibility of maximizing the digital economy. One thing that can still be improved is related to the sale of services, the tendency for online transactions to be more focused on transactions related to physical goods but with the opportunity to see and carry out transactions related to services, this can be done to gain an advantage and related improvements with business opportunities. Obstacles that tend to be found are related to trust because the service process requires someone to come to a location to carry out tasks, this is a challenge for the provision of AHS-Clean applications that provide shoe washing services. This research employs a qualitative approach, with case studies on several leading shoe companies that have implemented digital applications. Data were collected through in-depth interviews with stakeholders, documentation analysis, and direct observation of the business processes involved. The findings indicate that the implementation of digital applications in various operational areas of the shoe business, including digital marketing, e-commerce, and inventory management, has resulted in a positive impact on sales and operational efficiency. However, the primary challenges encountered pertain to the integration of new technologies with existing systems and the necessity to train employees to adapt to these digital changes.